Sistemas integrados de produção agropecuária : efluxo de gases e atividade microbiana do solo - Stieven, Ana Carla (2016)
This paper contains three chapters, at the first chapter the objective was to present the different forms of integrated management systems of agricultural production, with its applications and forms of soil microbiology and soil gases efflux; in the second chapter was developed to evaluate the soil samples from gás efflux from three different managements, integrated crop-livestock integration (ICL), pasture and native forest, with the glyphosate addition; the third chapter evaluated microbiological dynamics in soil under management with three different integrated crop-livestock-forest systems (ICLF), single, double and triple eucalyptus lines, and compared with pasture and native forest. Chapter 1 was developed from literature review, which sought to state of the art and the ICL and ICLF settings in order to differentiate these managements. In addition, the variables were presented used to monitor the microbial community in the soil, with respect to carbon held in the community and the variables derived from this, and to quantify the micro-organisms communities and evaluate soil enzymes activity. Another point was evaluated the dynamics of soil gases and initiatives to mitigate this efflux. The end is considered, the need for prior assessment for taking forward the decision to the managements, taking into account the objectives of each, which are grazing reform to ICL and maximum use of the area and insert the farmer in several production cadeis to ICLF. On the other hand, there is requirement to research these systems to prove the sustainable use and soil management employee in the area, preventing loss and burden of productivity and environmental in these locations. In chapter 2 it was carried out the evaluation of organic matter content, pH and electrical conductivity in pretreated soil, and treatment consisted of glyphosate application 4 L ha of in the from three different managements, ICL, pasture and native forest. After treatment the results obtained were CO2 and CH4 efflux from the closing cameras and infrared analysis. There was quantification of efflux for 10 days after application and the data were submitted to bootstrap analysis. It was concluded that the CO2 and CH4 efflux have been changed by different management systems adopted, and glyphosate addition reduces the efflux in all managements, especially in soil from native forest. Chapter 3 evaluated the soil microbiology and chemistry under three diferente ICLF systems, simple, double and triple eucalyptus lines, and compared them with pasture and native forest, in 0-20 cm depth, 2 years of evaluation. The results were submitted to multiple comparisons nonparametric analysis, correlation and regression between variables, and main components analysis. It was concluded the soil microorganisms enumeration and activity showed greater variation in relation to the year of collection that in relation to the adopted management; soil microbiology, in the realized managements, was mainly influenced by the potential acidity chemical attributes, organic matter and cation exchange capacity; magnesium was an important factor in the alkaline phosphatase and urease enzyme activity; it was noted the more time requeriment to review the systems for allocating assertive conclusions about the sustainability of the same.